2012
DOI: 10.1016/j.humimm.2011.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Association of IL28B gene polymorphism with development of hepatocellular carcinoma in Japanese patients with chronic hepatitis C virus infection

Abstract: IL28B single nucleotide polymorphisms (SNPs) are associated with spontaneous and treatment-induced elimination of hepatitis C virus (HCV). To assess whether the IL28B rs8099917 SNP also affects the progression of chronic HCV infection, we genotyped 511 Japanese HCV patients, including 69 with hepatocellular carcinoma (HCC). The T/T genotype of rs8099917 was not associated with the development of HCC (p = 0.623), although stepwise logistic regression analysis showed that liver cirrhosis, age greater than 68 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 15 publications
3
25
2
Order By: Relevance
“…A similar finding was reported that the C-allele has a protective role in the development of HCV-induced HCC and in HCV recurrence after liver transplantation [27]. On the contrary, other studies have reported that the variants of IL28B may not be involved in the hepatocarcinogenesis of HCV-infected patients [25, 28]. Results reported in the present study were in agreement with that of the latter studies as none of the five IL28B genetic variants investigated in this study had any significant effect on the advancement of HCV infection to cirrhosis and/or HCC; though, we did observe that these SNPs could have a significant role in the establishment of HCV infection as they showed significant differences in distribution between patients and healthy control subjects.…”
Section: Discussionsupporting
confidence: 74%
“…A similar finding was reported that the C-allele has a protective role in the development of HCV-induced HCC and in HCV recurrence after liver transplantation [27]. On the contrary, other studies have reported that the variants of IL28B may not be involved in the hepatocarcinogenesis of HCV-infected patients [25, 28]. Results reported in the present study were in agreement with that of the latter studies as none of the five IL28B genetic variants investigated in this study had any significant effect on the advancement of HCV infection to cirrhosis and/or HCC; though, we did observe that these SNPs could have a significant role in the establishment of HCV infection as they showed significant differences in distribution between patients and healthy control subjects.…”
Section: Discussionsupporting
confidence: 74%
“…In the context of HCC, two studies associated IFN-λ3 rs12979860 unfavorable CT or TT alleles with liver cirrhosis and the development of HCC in patients chronically infected with HCV (100, 101). However, this was not confirmed in two other independent studies in Japanese (102) or Italian cohorts (97). Finally, HCV-related liver disease is a multifactorial problem, and the independent association of genetic factors may not be a clear cut.…”
Section: Ifn-λ During Treatment With Direct-acting Antivirals (Daa) Amentioning
confidence: 69%
“…A large-scale European genome-wide association study (GWAS) recently identified a weak protective role for the rs12979860 T allele in the progression of fibrosis during HCV infection (37), whereas a Japanese GWAS identifying a susceptibility locus for HCV-induced HCC found no association of rs12979860 and rs8099917 SNPs with HCC (38). In support of these findings, Joshita and colleagues reported no association between the IL-28B genotype and the incidence of primary HCC (39). These results show a good concordance with those of the present study, which revealed that the IL-28B genotype was not associated with HCC incidence before treatment (Table 1).…”
Section: Discussionmentioning
confidence: 99%